2016
DOI: 10.3171/2016.8.focus16233
|View full text |Cite
|
Sign up to set email alerts
|

Laser interstitial thermal therapy followed by minimal-access transsulcal resection for the treatment of large and difficult to access brain tumors

Abstract: OBJECTIVE Laser interstitial thermal therapy (LITT), sometimes referred to as “stereotactic laser ablation,” has demonstrated utility in a subset of high-risk surgical patients with difficult to access (DTA) intracranial neoplasms. However, the treatment of tumors larger than 10 cm3 is associated with suboptimal outcomes and morbidity. This may limit the utility of LITT in dealing with precisely those large or deep tumors that are most difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Our results show that the complexity of medical comorbidities (as measured by the CCI) and the levels and stability of systolic blood pressure and blood glucose significantly predict postoperative morbidities in GBM patients. Previous studies reported associations between the extent of tumor resection and resection methods and postoperative complications . Our study results also concurred with the current literature that postoperative complications may negatively affect the delivering of adjuvant treatments for GBM patients .…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that the complexity of medical comorbidities (as measured by the CCI) and the levels and stability of systolic blood pressure and blood glucose significantly predict postoperative morbidities in GBM patients. Previous studies reported associations between the extent of tumor resection and resection methods and postoperative complications . Our study results also concurred with the current literature that postoperative complications may negatively affect the delivering of adjuvant treatments for GBM patients .…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Wright et al described the efficacy of transsulcal resection followed by LITT for optimization of EOR for large difficult-to-access intracranial neoplasms. 32 A combined approach to operative reduction of tumor burden can likewise achieve sufficient ablation/ resection in surgical candidates with partially deep-seated GBM, particularly for patients in whom a > 78% threshold of tumor resection/ablation cannot be achieved by resection or LITT alone.…”
Section: Discussionmentioning
confidence: 99%
“…Post-LITT edema may potentially be more fulminant than post-craniotomy edema due to the lack of any decompression with LITT alone. A prolonged steroid course (2–3 weeks) or a minimally invasive craniotomy and limited resection immediately following LITT of larger tumors may represent strategies to mitigate this phenomenon ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%